Influences of CdSe NCs on the photovoltaic parameters of BHJ organic solar cells - Ongul, Fatih; Yuksel, Sureyya Aydin; Allahverdi, Cagdas; Bozar, Sinem; Kazici, Mehmet; Gunes, Serap (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, the high quality CdSe nanocrystals (NCs) capped with stearic acid were synthesized in a solvent and then purified four times by using the precipitation and redissolution process. The average size of the synthesized CdSe NCs was determined similar to 3.0 nm via transmission electron microscopy (TEM) measurement and their corresponding optical band edge energy was also calculated as similar to 2.1 eV using ultraviolet-visible (UV-Vis) absorption spectroscopy. The bulk heterojunction (BHJ) hybrid solar cells based on a ternary system including P3HT, PCBM and CdSe NCs at different weight concentrations (0 wt%, 0.1 wt%, 0.5 wt%, 1 wt% and 2 wt%) were fabricated by spin-casting process. The effect of the concentration of CdSe NCs on the photovoltaic parameters of these BHJ organic solar cells was investigated. The surface morphology of the photoactive layer modified by the incorporation of CdSe NCs into P3HT:PCBM matrix was observed with scanning electron microscopy (SEM). It was shown that when the concentration of CdSe NCs increases above 0.1 wt% in this ternary system, the photovoltaic performance of the devices significantly decreases. The power conversion efficiency of the organic photovoltaic (OPV) device was enhanced similar to 20% by incorporating CdSe NCs with 0.1 wt% with respect to those without CdSe NCs. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: CdSe; Nanocrystals; BHJ; Organic solar cells; QUANTUM DOTS; POLYMER; ARCHITECTURES; PHOTOCURRENT; PURIFICATION; SPECTROSCOPY; EFFICIENCY